A systematic evaluation of polycyclic aromatic hydrocarbons in South Atlantic subtropical mangrove wetlands under a coastal zone development scenario. (1st January 2021) - Garcia, Marina Reback; Martins, César C.
Abstract: Mangrove forests worldwide are threatened environments considered vulnerable to chronic contamination by hydrophobic contaminants such as polycyclic aromatic hydrocarbons (PAHs). These ecosystems have a key role in the dynamics of biogenic and anthropogenic carbon storage and provide proper conditions for accumulation. One of most important subtropical mangrove swamps in the South Atlantic is located in the Paranaguá Estuarine System (PES), the largest bay of South Brazil surrounded by well-preserved Atlantic rainforests; however, the PES is under imminent risks of damage, e.g., due to incidental oil spills during port operations. In this scenario, PAHs were assessed for the first time in the mangrove sediments of the PES. The concentrations of 16 priority PAHs (EPA) (<DL – 234.3 ng g −1, 36 samples) were higher than those observed in previous studies for bottom sediments and had a similar order of magnitude as those for other human-impacted mangroves but were lower than those of other heavily impacted mangroves. A moderate level of anthropic contamination was observed, and the main probable sources of PAHs were navigation and domestic effluents. Bulk parameters (TOC/TN ratio and δ 13 C) showed the estuarine land-sea gradient and helped define the preferential sites of PAH deposition due to its correlation with TOC and fine sediments. Marine hydrodynamics and/or dilution processes had a major influence on PAH distribution, resulting in higher concentrations in the inner/sheltered areas of the estuary and lower values in the outer zone of the estuary with higher hydrodynamic energy. The environmental features and anthropogenic forcing of the PES added to the relative absence of a detailed evaluation of the levels of and environmental risks posed by PAHs in other subtropical mangrove ecosystems located in the Southern Hemisphere, reinforcing the importance of the current study. Graphical abstract: Image 1 Highlights: PAHs in mangrove sediments from a subtropical biosphere reserve were evaluated. PAH levels decreased with increasing hydrodynamic energy of the estuary. Perylene was the predominant compound attributed to diagenetic origin. The combustion of petroleum, attributed to navigation, was the main source of PAHs. Punctual sources of domestic effluents may cause higher levels of PAHs.